1997
DOI: 10.2151/jmsj1965.75.6_1091
|View full text |Cite
|
Sign up to set email alerts
|

Sea Surface Temperature in the South China Sea

Abstract: Interannual variability of the sea surface temperature anomalies (SSTA) over the South China Sea (SCS) is recognized as an index for the Asian monsoon and ENSO system because of its special geographical location for that system.The following results are obtained by the statistical analysis of the observational data.(1) In the northern winter, the SCS SSTA are quite sensitive to the longitudinal shift of global wind anomalies associated with the equatorial Pacific SSTA. This fact is related to that the SCS SSTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Abundant water exchange and complex atmospheric processes make the SCS susceptible to the Pacific and Indian Oceans but quite different from them (Liu et al, 2004;Chiang et al, 2018). Observational analyses have shown that the sea surface temperature in the SCS (SCS SST) exhibit abundance of multiple timescales from seasonal to decadal variabilities, which are largely modulated by the East Asian monsoon, El Niño-Southern Oscillation (ENSO), Interdecadal Pacific Oscillation, and global warming (Shen and Lau, 1995;Tomita and Yasunari, 1996;Ose et al, 1997;Chu et al, 1999;Klein et al, 1999;Qu, 2001;Chen et al, 2003;Wang et al, 2006a;Yu and Qu, 2013;Wu et al, 2014;Cheng et al, 2016;Cheng et al, 2017;Cheng et al, 2019;Xiao et al, 2020a;Liang et al, 2021). Among them, the impact of ENSO on the SCS SST on the interannual timescale has been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Abundant water exchange and complex atmospheric processes make the SCS susceptible to the Pacific and Indian Oceans but quite different from them (Liu et al, 2004;Chiang et al, 2018). Observational analyses have shown that the sea surface temperature in the SCS (SCS SST) exhibit abundance of multiple timescales from seasonal to decadal variabilities, which are largely modulated by the East Asian monsoon, El Niño-Southern Oscillation (ENSO), Interdecadal Pacific Oscillation, and global warming (Shen and Lau, 1995;Tomita and Yasunari, 1996;Ose et al, 1997;Chu et al, 1999;Klein et al, 1999;Qu, 2001;Chen et al, 2003;Wang et al, 2006a;Yu and Qu, 2013;Wu et al, 2014;Cheng et al, 2016;Cheng et al, 2017;Cheng et al, 2019;Xiao et al, 2020a;Liang et al, 2021). Among them, the impact of ENSO on the SCS SST on the interannual timescale has been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…The year-to-year correlations of the JRA-55 SLP EOF resolution coefficients with the previous northern winter (December-January-February mean; DJF mean) surface air temperature are shown in Figure 3d-f. The recent year-to-year variations in EOF1-2 exhibit the summer Asian monsoon anomalies after an El Niño winter (e.g., Ose et al 1997;Xie et al 2009), which are specifically warmer SST anomalies in the northern Indian and tropical northern Atlantic oceans (Fig. 3a-b), as well as the high-pressure anomalies to north of the Philippine Islands (Fig.…”
Section: Recent Year-to-year Variations In Other Fieldsmentioning
confidence: 99%
“…Tomita and Yasunari (1996) noticed that the SST in the SCS was closely linked to the SST in the equatorial central Pacific in wintertime. Ose et al (1997) analyzed observational data and found that the close relationship between the warm SST anomalies in summertime in the SCS and warm SST anomalies in the previous wintertime in the equatorial central Pacific may be established through the wind fields. After the 1997/98 super El Niño event, many studies have shown that the ENSO could lead by 5 months and affect the SST in the SCS (Klein et al 1999;Wang et al 2000).…”
Section: Introductionmentioning
confidence: 99%